PELATIHAN DIGITAL MINDSET & TRANSFORMASI USAHA DI ERA 5.0 KEPADA PELAKU USAHA DAN MAHASISWA WIRAUSAHA - Iskandar, Rizkiani; Kasim, Mohammad Yunus; Nurdin, Djayani; Fattah, Vitayanti; Darman, Darman; Buntuang, Pricylia Chintya Dwi; Asriadi, Asriadi; Utami, Ayu Putri; Evrianti, Hesti (LPPM Universitas Nusa Mandiri, 2026)
This community service program aims to strengthen digital mindsets and encourage business transformation in the Society 5.0 era for local business owners and student entrepreneurs in Palu City. The activity was designed as a participatory workshop that integrated the presentation of the Society 5.0 concept (a super-intelligent society that places humans at the center of technology-based innovation) and digital mindset (an adaptive way of thinking that utilizes digital technology as part of a long-term business strategy) with hands-on practice using digital applications for marketing and business management. Evaluation was conducted through pre- and post-tests, satisfaction questionnaires, and observations of 50 participants. The results showed an increase in the average score of understanding digital mindsets from 68,20 to 85,40, with 85% of participants stating that the activity was very beneficial and 75% stating that they were ready to implement business digitalization strategies. Student entrepreneur participants showed faster adaptation to digital applications compared to senior business owners, who still needed further mentoring. These findings indicate that strengthening digital mindsets combined with practical training has the potential to effectively encourage gradual digital-based business transformation and increase entrepreneurial competitiveness in Palu City in the Society 5.0 era.